Characterization of a grading system to evaluate splenic congestion. - Oliveira, A. L. (2013)
Background: Frequently, the spleen may be targeted by active hyperaemia, or acute or active congestion, common in acute systemic infections and in some acute bacterial intoxications, and also by passive congestion, or chronic congestion, due to disturbances in the systemic and portal circulation and, most commonly, due to the use of barbiturate drugs. An acutely congested spleen is enlarged, moderately turgid and cyanotic, with the capsule blue-black. The normal architecture is not discernible on the cut surface and the pulp is red-black and exudes blood. Microscopically, the red pulp sinusoids are dilated filled with packed red cells, the germinal centres are widely separated and trabeculae are thinned. With chronic congestion, the spleen becomes firm, the capsule and trabeculae thickened; there is lymphoid atrophy, sinus proliferation, with a marked increase in fixed cells in the red pulp and heavy sinus colonization with macrophages and hemosiderin, following RBC destruction in dilated sinusoids. Extend of the acute congestion may make histological examination difficult. In some species there is still some difficulty on determine the severity of spleen congestion and rule out other conditions like primary neoplastic lesions, metastatic disease or manifestation of systemic involvement, due to it specific circulation system. Objectives: The authors present an illustrated system to evaluate splenic congestion, using the pig as a model. Methods: Samples of the spleen of Large White Pigs were fixed in 10% neutral-buffered formalin, for a maximum of 48 hours, embedded in paraffin wax, and 3µm sections were stained for routine histopathological diagnosis with hematoxylin and eosine. All samples were examined by light microscopy, using a Microscope Zeiss Mod. Axioplan 2. Results: In this study, fourteen spleen samples from Large White pigs were observed and classified. The semi-quantitative parameter congestion was evaluated by two independent examiners and classified in a specific scale from 0 (minimal) to 3 (severe and extensive damage), from which exemplificative pictures will be presented, in order to better characterize the grading system used. Conclusion: Based on the description and pictures presented, the authors conclude that it was possible to clarify a classification grading system to evaluate splenic congestion, using the pig as a model, which can be used to evaluate splenic congestion in other domestic animals, as dogs and cats, which can be of great importance to characterize lesions in specific diseases and conditions.